Reporting completeness of the AIDS Case Reporting Surveillance System. - Whitehead, Jeffrey J. (University of Ottawa (Canada), 1997)
The problem. The AIDS Case Reporting Surveillance System (ACRSS) is a passive surveillance system that was initiated in 1982. It is used to follow the health impact of HIV in the population at large and to determine HIV prevalence through back-calculation. An assessment of the proportion of all AIDS cases reported out of all AIDS cases diagnosed (i.e., reporting completeness) was required as part of the evaluation of this surveillance system. Methods. A number of secondary data sources were considered; the use of death certificate data from the Canadian Mortality Data Base (CMDB) was chosen by a process of elimination. Reporting completeness to the AIDS Case Reporting Surveillance System is about 85% which compares well with that seen in other countries. Reporting completeness is lower for females than males. Reporting completeness varies by province with Quebec, P.E.I., and New Brunswick having the lowest rates of reporting. Alberta and Ontario have the highest rates of reporting. Reporting is less complete in those that die in smaller communities. Reporting completeness decreased slightly during the 1980s. The most important finding is the trend to increased underreporting with time. Future validations of reporting completeness will become more difficult in Quebec due to the lack of initials on their dataset. The causes of incomplete reporting will only be elucidated with qualitative investigation. (Abstract shortened by UMI.)
Keywords: Health Sciences, Public Health.